2009
DOI: 10.1097/sap.0b013e31818bed6d
|View full text |Cite
|
Sign up to set email alerts
|

Parry-Romberg Syndrome

Abstract: Parry-Romberg syndrome (PRS) is an uncommon disorder and characterized by a slowly, an acquired progressive atrophy involving skin, soft tissue, cartilage, and bony structures. Accompanying atrophies of the other parts of the body are rarely reported. The aim of this study is to report a case that had contralateral lower extremity atrophy with PRS, and to review the related etiologic features, physiopathology, and mechanism. The patient who admitted for his facial atrophy also had atrophy of his contralateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…In the situations evaluated for this study, there was a higher occurrence of atrophy in the buccinator muscle region and no incidence of atrophy in the masseter muscle region. However, a previous study (6) reported the case of a patient with Parry-Romberg syndrome who presented with atrophy of the sternocleidomastoid, masseter and pterygoid muscles and of the subcutaneous soft tissues, though these findings were revealed via magnetic resonance imaging (MRI) rather than EMG. To validate these results, the test should be repeated, adding the buccinator muscle region to the data collection and analysis.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In the situations evaluated for this study, there was a higher occurrence of atrophy in the buccinator muscle region and no incidence of atrophy in the masseter muscle region. However, a previous study (6) reported the case of a patient with Parry-Romberg syndrome who presented with atrophy of the sternocleidomastoid, masseter and pterygoid muscles and of the subcutaneous soft tissues, though these findings were revealed via magnetic resonance imaging (MRI) rather than EMG. To validate these results, the test should be repeated, adding the buccinator muscle region to the data collection and analysis.…”
Section: Discussionmentioning
confidence: 96%
“…In Parry-Romberg syndrome, the individuals show normal craniofacial growth until the onset of the first signs, which normally occurs in the first two decades of life (2)(3)(4)6,7,10,11,13) . Normal craniofacial growth may explain why there were no significant differences regarding the static measurements of the face, even when dealing with a syndrome whose main characteristic is facial asymmetry (4,13) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations